AUDIT OPERASIONAL TERHADAP FUNGSI PENJUALAN BARANG DAGANG UNTUK MENGUKUR EFISIENSI DAN EFEKTIVITAS PADA KOPERASI UNIT DESA MAMBAL DI KABUPATEN BADUNG - Luh Putu Vina Indah Perdanawati; Nyoman Dwika Ayu Amrita (Jurnal Riset Akuntansi (JUARA), 2018)
Economic is growing rapidly creates business opportunities for cooperatives in an effort to manageand expand its business operations. Cooperative operational development requires aninternal control system by cooperative management so that cooperative can generate maximumprofit, especially in the sales process. Internal control of the sales process is important becausesales are one of the elements of property in the component of profit and loss. The internalcontrol system in the sales function is conducted through internal audit, especially the salesoperation examination, which aims to assess the compliance with the policies or sales proceduresestablished by the cooperative, evaluate the level of efficiency and effectiveness so thatthe cooperative can know the constraints and weaknesses encountered in sales activities. KUDMambal is a cooperative that has a main field in the process of selling rice transactions, whilefor penjulan fertilizer only get a fee only from each transaction. This study aims to determinethe efficiency and effectiveness of the sales function of the operational audit of Mambal VillageUnit Cooperative and to know the analysis of operational audit results of the Village Unit CooperativeMambal. Methods of data collection is a systematic way through Library Studies (LibraryResearch and Field Studies (Field Research), namely by direct observation (observation), andinterviews directly (interview). Data analysis techniques carried out were preliminary surveys,planned audits, conducted audits and reported findings in the form of audit reports. Based onthe research found the problem is the absence of written SOP, the dual position between the treasurerdoubles as head of sales. Nevertheless it can be concluded that KUD Mambal has donea good internal control related to the sales function is indicated by the use fomulir barupa notesheet and evidence of cash expenditure on each transaction and the pricing of a price using aprice based on the price of PERPADI Badung regency, and has been internal monitoring throughperiodic evaluations every 3 (three) months against the target penjulannya so that operationalaudit of the sales function merchandise has an important role in measuring the efficiency andeffectiveness seen from the survey and questionnaire research.